Downregulation of androgen receptors by NaAsO2 via inhibition of AKT‐NF‐κB and HSP90 in castration resistant prostate cancer. Issue 10 (30th May 2017) - Kim, Yunlim; Park, Sang Eun; Moon, Jeong‐Weon; Kim, Bong‐Min; Kim, Ha‐Gyeong; Jeong, In Gab; Yoo, Sangjun; Ahn, Jae Beom; You, Dalsan; Pak, Jhang Ho; Kim, Sujong; Hwang, Jung Jin; et al.
Abstract : Background: Androgen and androgen receptor (AR) play essential roles in the development and maintenance of prostate cancer. The recently identified AR splice variants (AR‐Vs) have been considered as a plausible mechanism for the primary resistance against androgen deprivation therapy (ADT) in castration‐resistant prostate cancer (CRPC). Sodium meta ‐arsenite (NaAsO2 ; KML001; Kominox), a trivalent arsenical, is an orally bioavailable and water soluble, which is currently in phase I/II clinical trials for the treatment of prostate cancer. It has a potent anti‐cancer effect on prostate cancer cells and xenografts. The aim of this study was to examine the effect of NaAsO2 on AR signaling in LNCaP and 22Rv1 CRPC cells. Methods: We used hormone‐sensitive LNCaP cells, hormone‐insensitive 22Rv1 cells, and CRPC patient‐derived primary cells. We analyzed anti‐cancer effect of NaAsO2 using real‐time quantitative reverse transcription‐PCR, Western blotting, immunofluorescence staining and CellTiter Glo® luminescent assay. Statistical evaluation of the results was performed by one‐way ANOVA. Results: NaAsO2 significantly reduced the translocation of AR and AR‐Vs to the nucleus as well as their level in LNCaP and 22Rv1 cells. Besides, the level of the prostate‐specific antigen (PSA), downstream target gene of AR, was also decreased. This compound was also an effective modulator of AKT‐dependent NF‐κB activation which regulates AR. NaAsO2 significantly inhibited phosphorylation of AKT and expression and nuclear translocation of NF‐κB. We then investigated the effect of NaAsO2 on AR stabilization. NaAsO2 promoted HSP90 acetylation by down‐regulating HDAC6, which reduces the stability of AR in prostate cancer cells. Conclusions: Here, we show that NaAsO2 disrupts AR signaling at multiple levels by affecting AR expression, stability, and degradation in primary tumor cell cultures from prostate cancer patients as well as CRPC cell lines. These results suggest that NaAsO2 could be a novel therapeutics for prostate cancer.